'Prophets of Doom': The Zimbabwean Christian Community and Contemporary Politics. Issue 2 (July 2017) - Hove, Mediel; Chenzi, Vincent
Since Zimbabwe's independence in 1980, the Christian community was largely silent about Zimbabwe's economic and political quagmire. However, the country's growing political and economic turmoil drew the Zimbabwean Christian community into direct confrontation with Mugabe's administration. The community experienced political awakening after decades of political indifference, passivity and silence. In 2016, several Christian leaders and their denominations publicly challenged the government on several occasions calling for Mugabe to step down and demanded economic reforms. In response, the Mugabe regime employed different tactics to silence and undermine the Christian community.